Toward the Green Economy: Assessing Countries' Green Power - Babette Never (German Institute of Global and Area Studies (GIGA), 2013)
The green power potential of a country is a central factor in the transformation to a green economy. This paper argues that green power will become a decisive factor for global change. Green power combines sustainability, innovation and power into one concept. By merging insights from political science, economics and innovation research, this paper develops a multidimensional, multilevel concept of green power that takes both resources and processes into account. A first empirical assessment of the current distribution of green power in global environmental governance shows that China and India, in particular, as well as Brazil and Costa Rica are catching up in clean technology and renewable energy. The European Union, Germany and the United States still dominate, but they are not fully maximizing their green power potential. In spite of their discursive power, the green power potential of the least developed countries is relatively small, making the jump toward a green economy unlikely.
Keywords: A12; F02; F59; F64; O32; O44; 330; climate change; power; global environmental governance; innovation; green economy